Peran Diplomasi Pertahanan Indonesia dalam Mendukung Kerja Sama dengan China untuk Mengatasi Pandemi Covid-19 - Budhi Tri Suryanti; Tri Legionosuko; Muhammad Halkis (CV. AFDIFAL MAJU BERKAH, 2023)
The Covid-19 pandemic left many nations in a dilemma to protect their respective countries. Indonesia carried out diplomacy with various countries that had the capability to help Indonesia overcome the pandemic through various diplomatic channels, one of which was China, even though it closed itself at the start of the pandemic. The involvement of military in carrying out the action shows the role of defense diplomacy in the cooperation between Indonesia and China to deal with the Covid-19 pandemic. The problem being studied is the role of Indonesia's defense diplomacy in supporting Indonesia-China cooperation in overcoming the pandemic; along with the contributing and inhibiting factors in the cooperation. The aim of the research is to analyze the role of Indonesian defense diplomacy in Indonesia-China cooperation along with the contributing and inhibiting factors in this cooperation. The research method used is qualitative method. Primary data was obtained through individual interviews and secondary data through library research. The results revealed that Indonesia's defense diplomacy played a role in supporting the activities of the Ministry of Health, and supporting the Ministry of Foreign Affairs. The contributing factors are China's help during the pandemic and military utilization in pandemic relief. The inhibiting factors are the prevalence of misinformation, the lack of preparedness in dealing with health threats, and the facilities, personnel and communication that are not yet optimal.